Identifikasi Mikroskopis Jamur dari Limbah Manihot Esculenta dengan Teknik Pewarnaan Gram A (Kristal Violet) - Keila Ramadhani; Ardi Mustakim (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
This study aims to identify the microscopic structure of fungi growing in Manihot esculenta (cassava) waste using Gram A (crystal violet) staining. Cassava waste is a type of organic waste that has the potential to serve as a growth medium for various microorganisms, including fungi. Microscopic observations were conducted to determine the morphology of fungal cells that grow naturally in the waste. The Gram staining method was used to facilitate visualization of the fungal cell wall structure, with an emphasis on crystal violet staining as the primary dye. Waste samples were fermented for 3–5 days to allow fungal growth, then taken and microscopic slides were made. The results showed the presence of purplish-purple fungal hyphae and spores, indicating that the fungal cells were able to retain the crystal violet stain. This structure indicates that the type of fungus growing has a thick cell wall and is likely included in the Ascomycota or Zygomycota group. This identification demonstrates the potential use of Manihot esculenta waste as a substrate for microbiological studies and the development of fungal-based biotechnology. This study also emphasizes the importance of simple staining techniques in assisting the initial identification of microorganisms in organic media.